1997
DOI: 10.1007/s004670050320
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in Henoch-Schönlein purpura

Abstract: The pathogenetic mechanism underlying Henoch-Schönlein purpura (HSP) is poorly understood. Complement activation has been thought to have a role, but despite the demonstration of complement components in skin and renal biopsy material, serological evidence of complement activation is not convincing. We have assessed complement activation in 64 children with acute HSP. We used an enzyme-linked immunosorbent assay to measure plasma levels of three multimolecular complement activation protein (CAP) complexes: C1r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
2
23
2
2
Order By: Relevance
“…Finally, serum SC5b-9 has been shown to correlate with the disease activity in patients with HSP [11]. In contrast to these reports, a study of 64 children with acute HSP failed to demonstrate any signi®cant dierence in the levels of C1r:C1s:C1 esterase inhibitor, C3bP and C5b-9 complexes between the patients and the controls [20]. Even though several studies have demonstrated activation of C3 and C4 in HSP, they failed to ®nd a corresponding reduction in serum concentrations of C3 and C4, which remained normal or elevated.…”
Section: Discussionmentioning
confidence: 77%
“…Finally, serum SC5b-9 has been shown to correlate with the disease activity in patients with HSP [11]. In contrast to these reports, a study of 64 children with acute HSP failed to demonstrate any signi®cant dierence in the levels of C1r:C1s:C1 esterase inhibitor, C3bP and C5b-9 complexes between the patients and the controls [20]. Even though several studies have demonstrated activation of C3 and C4 in HSP, they failed to ®nd a corresponding reduction in serum concentrations of C3 and C4, which remained normal or elevated.…”
Section: Discussionmentioning
confidence: 77%
“…However, an activation of the complement occurs since degradation products have been demonstrated in plasma and glomeruli [20, 22]. However, the role of this activation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, an activation of the complement cascade does occur since degradation products have been demonstrated in plasma and glomeruli [15,40,76]. The role of this activation remains however unclear.…”
Section: Complementmentioning
confidence: 98%
“…The role of this activation remains however unclear. Results of studies attempting to correlate the level of complement split products in the blood with clinical signs [15,40,76] or the glomerular deposition of various complement factors and histological lesions are contradictory [26].…”
Section: Complementmentioning
confidence: 99%